2020
DOI: 10.21203/rs.2.22998/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Youth unemployment and mental health: Prevalence and associated factors of depression among unemployed young adults in Gedeo zone, Southern Ethiopia

Abstract: Background: The high rate of unemployment among young adults in Ethiopia (25.3%) is a public health concern. The risk of mental health problems like depression is higher among the unemployed than among the employed. However, there is no study conducted on the prevalence and associated factors of depression among unemployed young adults in Ethiopia. Hence, this study is aimed to assess the prevalence and associated factors of depression among unemployed young adults in Gedeo zone, Southern Ethiopia.Methods: Com… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This result is supported by other studies revealing that unemployed individuals are more likely to report psychological symptoms. 11,23 This finding may elucidate additional stressors, such as severe financial hardship and poverty, debt, boredom, homelessness, and the loss of confidence and self-esteem that people with substance use disorders may have to endure. 23 Thus, government and health authorities should develop appropriate intervention strategies and policy guidelines to protect and preserve the psychological health of those susceptible to psychological symptoms.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This result is supported by other studies revealing that unemployed individuals are more likely to report psychological symptoms. 11,23 This finding may elucidate additional stressors, such as severe financial hardship and poverty, debt, boredom, homelessness, and the loss of confidence and self-esteem that people with substance use disorders may have to endure. 23 Thus, government and health authorities should develop appropriate intervention strategies and policy guidelines to protect and preserve the psychological health of those susceptible to psychological symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…Expectedly, and as established in previous studies, we found that the presence of a pre-existing medical condition was highly associated with psychological symptoms, including depression, anxiety, and stress. 18,23 A significant body of epidemiologic studies highlights that the solo presence of medical conditions, such as cancer, Diabetes Mellitus (DM), and HIV, is associated with poor mental health. 25,26 Hence, people with substance use disorders having pre-existing medical condition should be identified and treated at the earliest to circumvent additional medical conditions and their psychosocial sequelae.…”
Section: Discussionmentioning
confidence: 99%